PRIMARY EDUCATION AND ITS ADVANTAGES - Rasulova Oysha (Journal of new century innovations, 2023)
Annotation: Nowadays, beginner is talking a lot about the integration of school education. This is understandable – a small schoolboy perceives the surrounding world as a whole. It’s not the name of Natural Science, Russian language, music and other educational subjects; there is a different nebula of sounds, volumes of the objects of the universe. Teaching children to see the connection of nature and all things in everyday life, the teacher perceives, knows.